Evaluation of the dynamic responses of truss spar platforms for various mooring configurations with damaged lines - Ahmed, M.O. (Elsevier Ltd, 2016)
Safe mooring for any platform is of utmost importance and concern because of the number of accidents as well as lack of knowledge due to uncertainties in the mooring lines behavior. This has led researchers to investigate the possible effect on the responses of a floating platform due to mooring line damages. Hence, this paper addresses the responses of a truss spar platform for various symmetric and asymmetric mooring configurations when one and two lines attached are damaged. To investigate this effect, the platform has been modeled as a three degree-of-freedom rigid structure and its motions are analyzed in time-domain. The forceâexcursion relationship of mooring lines is determined using quasi-static approach. It is observed that the effect of damaged mooring lines on symmetric and asymmetric configurations is nearly same. The migration distance of platform is considerably significant due to the damaged lines. It is more than thrice when two lines are damaged compared to one damaged line condition for symmetric and asymmetric configurations. However, the dynamic motions are not significantly affected. Â© 2016 Elsevier Ltd